Acute infection with Brachyspira hyodysenteriae affects mucin expression, glycosylation, and fecal MUC5AC - Lin, Susanne Je-Han; Helm, Emma T.; Gabler, Nicholas K.; Burrough, Eric R. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Infection with strongly β-hemolytic strains of Brachyspira hyodysenteriae leads to swine dysentery (SD), a production-limiting disease that causes mucohemorrhagic diarrhea and typhlocolitis in pigs. This pathogen has strong chemotactic activity toward mucin, and infected pigs often have a disorganized mucus layer and marked de novo expression of MUC5AC, which is not constitutively expressed in the colon. It has been shown that fucose is chemoattractant for B. hyodysenteriae, and a highly fermentable fiber diet can mitigate and delay the onset of SD. Methods We used lectins targeting sialic acids in α-2,6 or α-2,3 linkages, N-acetylglucosamine (GlcNAc), α-linked L-fucose, and an immunohistochemical stain targeting N-glycolylneuraminic acid (NeuGc) to investigate the local expression of these mucin glycans in colonic tissues of pigs with acute SD. We used a commercial enzyme-linked immunosorbent assay (ELISA) to quantify fecal MUC5AC in infected pigs and assess its potential as a diagnostic monitoring tool and RNA in situ hybridization to detect IL-17A in the colonic mucosa. Results Colonic mucin glycosylation during SD has an overall increase in fucose, a spatially different distribution of GlcNAc with more expression within the crypt lumens of the upper colonic mucosa, and decreased expression or a decreased trend of sialic acids in α-2,6 or α-2,3 linkages, and NeuGc compared to the controls. The degree of increased fucosylation was less in the colonic mucosa of pigs with SD and fed the highly fermentable fiber diet. There was a significant increase in MUC5AC in fecal and colonic samples of pigs with SD at the endpoint compared to the controls, but the predictive value for disease progression was limited. Discussion Fucosylation and the impact of dietary fiber may play important roles in the pathogenesis of SD. The lack of predictive value for fecal MUC5AC quantification by ELISA is possibly due to the presence of other non-colonic sources of MUC5AC in the feces. The moderate correlation between IL-17A, neutrophils and MUC5AC confirms its immunoregulatory and mucin stimulatory role. Our study characterizes local alteration of mucin glycosylation in the colonic mucosa of pigs with SD after B. hyodysenteriae infection and may provide insight into host-pathogen interaction.